A new species of Sigmaxinella Dendy, 1897 (Demospongiae, Poecilosclerida, Desmacellidae) from the Tasman Sea - Mitchell, Kirsty D.; Hall, Kathryn A.; Hooper, John N. A. (Zootaxa, 2011)
Sigmaxinella hipposiderus sp. nov. is described from morphological and molecular datasets, based on a single known specimen collected from the upper margin of a submarine canyon on the edge of the continental shelf, south-east of coastal Victoria (Tasman Sea), Australia. Morphologically, the species is clearly assigned to the genus Sigmaxinella, and preliminary molecular data (COI mt DNA) support the close relationship of this new species to other specimens attributed to Desmacellidae. This is the thirteenth species of Sigmaxinella and the seventh described for the Australian EEZ. Remarkably, 12 of the 13 known species are recorded predominantly from temperate or subantarctic Australian, New Zealand or South African waters, with only a single species described so far from the temperate Atlantic Ocean.